Relevance and Challenges for Vocational Education Toward Demographic Dividend in Indonesia - Mochamad Iqbal Jatmiko (Indonesian Journal of Economics, Social, and Humanities, 2019)
The writing of this paper is motivated by the transformation of vocational-based education in the face of demographic dividend and possible problems. This phenomenon is very important to be studied more deeply as an effort to see the success and challenges of vocational education in Indonesia. This article argues that there is a productive relationship between increasing vocational education through vocational secondary schools and diplomas with demographic dividend transitions. This can be seen in the data which show that there is a decline in the unemployment rate in Indonesia, especially for vocational high school graduates; as an impact of improving the quality and quantity of vocational education. The writing of this article uses qualitative methods with the support of secondary data from the Central Statistics Agency and literature studies of various sources related to the issue of study. In the results of the discussion, it was found a new discussion about the role of the government in anticipating the increasingly rapid context of the technological era so that there was no higher educated unemployment. The distribution of inter-regional policies and strengthening in technology qualifications are also potential sources that must be developed again so that the demographic transition can result in improvements in the country's economy.